Recasting World War II: Using Oral Histories To Understand The "Greater War" - Kneeshaw, Stephen (Teaching History: A Journal of Methods, 1995)
As we observe the fiftieth anniversary of the close of World War Il, historians and popular authors are churning out countless books about the war and the men and women whose lives were shaped and sometimes changed unalterably by this "greater war" of the twentieth century.1 These studies run from biographies and psychological inquiries to diplomatic and military histories of key moments in the war to full-scale studies of the conflict in Europe and the Pacific. They surely will change the way we think about the world of the 1930s and 1940s and the way we teach World War II.